ANALISIS PENGARUH MULTI-FEEDSTOCK BIODIESEL TERHADAP PERFORMA FOUR-STROKE DIESEL ENGINE DENGAN LSCS PISTON - Faruq As'ary; Edi Haryono; Lely Pramesti (Proceedings Conference on Marine Engineering and its Application, 2023)
Biodiesel emerges as a promising solution that can be pursued domestically. This fuel canbe produced from available vegetable oil and animal fat resources. In the context of this research, thefocus is on creating multi-feedstock biodiesel from palm oil, corn oil, and coconut oil. Subsequently,blends of these various biodiesel types are mixed with Pertamina Dex to produce fuels in the forms ofB20, B35, and B100. Tests were conducted on a four-stroke diesel engine utilizing the LSCS piston.The tested variables encompassed engine loads at levels of 1000 Watts, 2000 Watts, and 3000 Watts,as well as engine speed variations at 900 rpm, 950 rpm, 1000 rpm, and 1050 rpm. Within this context,the research's objective was to examine the characteristics of the applied biodiesel and its impact onengine performance. The test results indicate that biodiesel with a B100 blend is capable of meetingIndonesian National Standard (SNI) requirements for flash point, cetane number, calorific value,density, and viscosity. Furthermore, in terms of engine performance, biodiesel with a B20composition has proven to provide optimal results in generating the required power and torque.Moreover, B20 also demonstrates the best performance in achieving the desired gsfc value.